The Effect of Synthetic Hydrated Calcium Aluminate Additive on the Hydration Properties of OPC - Jolanta Doneliene; Anatolijus Eisinas; Kestutis Baltakys; Agne Bankauskaite (Advances in Materials Science and Engineering)
The effect of synthetic CAH (130°C; 8 h; CaO/(SiO2 + Al2O3) = 0.55; Al2O3/(SiO2 + Al2O3) = 0.1, 0.15) with different crystallinity on the hydration kinetics of OPC at early stages of hydration was investigated. Also, the formation mechanism of compounds during OPC hydration was highlighted. It was determined that the synthetic CAH accelerated the initial reaction and shortened the induction period. Also, the second and third exothermic reactions begun earlier, and, during the latter reaction, the higher values of the heat flow were obtained in comparison with pure OPC samples. At later stages of hydration, synthetic CAH affect the OPC hydration as the usual pozzolanic additives; moreover, the larger values of cumulative heat were reached. It should be noted that the nature of synthetic CAH samples accelerated the dissolution of gypsum and stimulates the earliest C3S hydration.